2019
DOI: 10.1016/j.eurpsy.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation and non-suicidal self-injury: A systematic review and meta-analysis

Abstract: Background:Over the past several years there has been considerable interest in the relation between emotion dysregulation and non-suicidal self-injury (NSSI), particularly given that rates of NSSI have been increasing and NSSI is a critical risk factor for suicidal behavior. To date, however, no synthesis of empirical findings exists.Methods:The present study presents a comprehensive meta-analytic review of the literature on the association between NSSI and emotion dysregulation. A total of 48 publications, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
151
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(231 citation statements)
references
References 101 publications
23
151
2
6
Order By: Relevance
“…These findings, as summarized in recent meta-analyses, support the emotion dysregulation hypothesis (e.g., Wolff et al, 2018), yet it is important to note that some sources of evidence are less conclusive. For example, although numerous studies demonstrate low parasympathetic nervous system (PNS) tone and excessive PNS withdrawal during negative emotion inductions among those who engage in NSSI and SBs (Crowell, Baucom, et al, 2014; Crowell et al, 2005, 2008, 2013, 2014, 2017; Kuo & Linehan, 2009), autonomic hyperreactivity is not as consistent when using (a) other markers, such as sympathetic nervous system (SNS) responding, and (b) non–emotion induction paradigms, such as cold-pressor, acoustic startle, and public speaking tasks.…”
Section: Traditional Conceptualizations Of Nssi and Suicidal Behaviormentioning
confidence: 65%
“…These findings, as summarized in recent meta-analyses, support the emotion dysregulation hypothesis (e.g., Wolff et al, 2018), yet it is important to note that some sources of evidence are less conclusive. For example, although numerous studies demonstrate low parasympathetic nervous system (PNS) tone and excessive PNS withdrawal during negative emotion inductions among those who engage in NSSI and SBs (Crowell, Baucom, et al, 2014; Crowell et al, 2005, 2008, 2013, 2014, 2017; Kuo & Linehan, 2009), autonomic hyperreactivity is not as consistent when using (a) other markers, such as sympathetic nervous system (SNS) responding, and (b) non–emotion induction paradigms, such as cold-pressor, acoustic startle, and public speaking tasks.…”
Section: Traditional Conceptualizations Of Nssi and Suicidal Behaviormentioning
confidence: 65%
“…Emotion dysregulation is a frequently cited risk factor for both non-suicidal self-injury (NSSI) and suicidal behaviour [ 30 , 31 ]. From a community study through self-report questionnaires and semi-structured interview about NSSI behaviours, Kranzler et al found that emotion dysregulation was indirectly associated with suicide attempt frequency, via internalising symptoms and NSSI frequency, suggesting that when faced with stress or negative affect, individuals with emotion regulation deficits may be less able to tolerate these difficult emotions and more likely to internalise their distress [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…People who self‐harm have been found to have difficulties in emotion regulation (Wolff, Thompson, Thomas, Nesi, Bettis & Ransford, 2019) and the empirical and theoretical literature positions self‐harm as a means of regulating unwelcome emotional experience (Chapman, Gratz & Brown, 2006; Klonsky, 2007; McKenzie & Gross, 2014). The association between self‐harm and alexithymia may be due in part to a lack of recourse to more adaptive regulation strategies.…”
Section: Introductionmentioning
confidence: 99%